(untitled) (INNOVATIVE ECONOMY, 2025)
Prushkivska E.V., Prushkivskyi V.H., Bondarenko L.A. SOCIAL ENTREPRENEURSHIP AS A SOCIAL POLICY TOOL: INTERNATIONAL EXPERIENCE AND PROSPECTS FOR UKRAINE Purpose. The purpose of the article is to clarify the role of social entrepreneurship as a tool of social policy in the international and national context. Methodology of research. In the course of the research, a systematic and comparative analysis was used, which made it possible to consider social entrepreneurship as a component of social policy in the context of global and national transformations. A comparative analysis of regional models (EU, Southeast Asia, Latin America, Ukraine) was used to identify common and distinctive features of the inclusion of social enterprises in socio-political strategies. The empirical basis of the study consisted of reports from international organisations (UNDP, OECD, European Commission), national statistical materials and scientific research. Content analysis of regulatory and legal acts and strategic documents made it possible to assess the institutional environment in which social enterprises operate. The generalisation of the results obtained made it possible to identify the conceptual functions of social entrepreneurship in the current socio-economic conditions. Findings. It has been established that in EU countries, social entrepreneurship is considered part of employment and inclusion policy, while in Southeast Asia, this type of entrepreneurship is focused on mobilising local communities and partnerships with international organisations. Latin America demonstrates the advantages of community models that combine innovation and the fight against poverty, but at the same time face political and economic instability. In Ukraine, social entrepreneurship is at the stage of institutional formation, but shows high potential for solving problems of employment, inclusion and social integration. Three conceptual functions of social entrepreneurship in the socio-economic strategies of countries have been identified: a tool for job creation, a mechanism for social inclusion, and a platform for partnership between the state, business and civil society. Originality. The research results provide grounds for substantiating the relationship between social entrepreneurship and social policy, which allows it to be interpreted not only as an innovative business model, but also as a multifunctional tool for achieving social sustainability. Unlike existing studies, the results integrate global, regional and national dimensions, identifying a typology of models and determining the prospects for their adaptation in Ukraine. Practical value. The results obtained can be used in the development of state and local social policy programmes aimed at supporting vulnerable groups, restoring the labour market and strengthening social integration. For Ukraine, in the context of war and post-war reconstruction, social entrepreneurship can become a mechanism for combining economic recovery with the formation of an inclusive society. Key words: civil society, inclusion, employment, international experience, social entrepreneurship, social policy, institutional support, post-war reconstruction.